CYCLIC VOLTAMMETRIC STUDY OF ELECTRO-OXIDATION OF METHANOL ON PLATINUM ELECTRODE IN ACIDIC AND NEUTRAL MEDIA - A. Khan, A. S.; Ahmed, R.; Mirza, M. L. (The Nucleus, 2020)
The electro-oxidation of methanol on electrochemically treated platinum foil was investigated in acidic and neutral media for comparison of cyclic voltammetric characteristics and elucidation of mechanism of electro-oxidation of methanol. The surface area and roughness factor of platinum electrode was calculated. The electro-oxidation of methanol is an irreversible process giving anodic peaks in both anodic and cathodic sweep. The characteristic peaks of electro-oxidation of methanol appeared at almost the same potential region in both acidic and neutral media. In neutral medium, certain additional cathodic/anodic peaks appeared which were confirmed to arise by the reduction/oxidation of hydrogen ions. The exchange current density and heterogeneous electron transfer rate constant was higher in neutral medium as compared with acidic medium. The thermodynamic parameters Î”H*, Î”S*, and Î”G298* were calculated. The values of Î”H* and Î”G298* were positive which indicated that the process of electro-oxidation of methanol is an endothermic and non-spontaneous. The mechanism of electro-oxidation of methanol was same in both acidic and neutral media involving the formation of various adsorbed intermediate species through dissociative adsorption steps leading to the formation of CO adsorbed radicals, which are removed during interaction with adsorbed hydrous oxides provided by the oxidation of adsorbed water molecules. The higher rate of electro-oxidation of methanol in neutral medium was interpreted in the light of electrochemical mechanism and was attributed to the presence of comparatively small amount of hydrogen ions only along the surface of working electrode, which are produced during electro-oxidation of methanol.